PENGARUH PENDIDIKAN KARAKTER DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP SOFT SKILL MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FPIPS IKIP PGRI BALI (Widyadari : Jurnal Pendidikan, 2021)
The purpose of this study was to determine (1) the significant effect of Character Education on the Soft Skills of Prospective Teacher Students in the Economic Education Study Program of FPIPS PGRI Bali, (2) the significant effect of Entrepreneurship Education on the Soft Skills of Prospective Teacher Students of the FPIPS IKIP PGRI Economic Education Study Program. Bali, (3) the significant influence of Character Education on the Soft Skills of Prospective Teacher Students in the Economic Education Study Program, FPIPS, IKIP PGRI Bali. The population in this study were students of class 2017, amounting to 78 people. Furthermore, the technical data analysis used is testing with regression analysis to find the F price, and then it can be tested whether the F price is significant or not. And the conclusion of this research is that Character Education (X1) has a positive and significant effect on Student Soft Skills. This is evidenced by the value of t-count = 9,462> t-table = 1.99 and the value of Sig. = 0.000 <0.05. Entrepreneurship Education (X2) has a positive and significant effect on Student Soft Skills. This is evidenced by the value of t-count = 4.255> t-table = 1.99 and the value of Sig. = 0.000 <0.05. Character Education (X1) and Entrepreneurship Education (X2) simultaneously influence student soft skills. This is evidenced by the value of F-count = 84.289> F-table = 3.12 and the value of Sig. = 0.000 <0.05.